Eclipse - Meyer, Stephenie, 1973- (Little, Brown, 2008)
Bella must choose between her friendship with Jacob, a werewolf, and her relationship with Edward, a vampire, but when Seattle is ravaged by a mysterious string of killings, the three of them need to decide whether their personal lives are more important than the well-being of an entire city.